Capital social y pobreza multidimensional, el caso de hogares pobres en Monterrey, México - Luis Portales (Universidad Autónoma del Estado de México, 2014)
The Metropolitan Area of Monterrey, despite having higher development indicators than most of the cities in Mexico, presents households in poverty conditions similar to those observed in the poorest regions of the country. In this context, this study presents the relationship between the households social capital located in a neighborhood with high levels of social backwardness and poverty levels. For this purpose, an ethnographic technique called personal networks and statistical analysis were used to observe how households with higher levels of poverty use their social capital as a living strategy that responds to the social need they have, and the way in which households with lower levels of poverty make use of amore strategic social capital that allows them to access a wider range of economic, social and institutional resources.